Further studies on Mouthpart Receptors in decapoda crustacea - Dando, M. R.; Moulins, M.; Laverack, M. S. (Zeitschrift fr Vergleichende Physiologie, 1970)
In the lobster Homarus gammarus (L.) (= Homarus vulgaris M. Ed.) three bilateral groups of proprioceptors are arranged around the mouth. These strand receptor organs, termed Mouthpart Receptors (MPRs) 1, 2 and 3, were described previously and their physiological responses, mainly to mandibular movements, were characterised (Laverack and Dando, 1968). Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/47103/1/359_2004_Article_BF00298189.pdf